The lost city of Faar - MacHale, D. J. (New York, N.Y. : Aladdin Paperbacks, 2003)
Bobby finds himself in the territory of Cloral, a world entirely covered by water, which is nearing a huge disaster. He learns that it is up to him to help rid the area of marauders and locate the legendary lost land of Faar, which may hold the key to Cloral's survival.
650
Accelerated Reader AR
Keywords: Heroes -- Fiction; Space and time -- Fiction; Fantasy fiction; Science fiction